Premis Kampus Merdeka: Perspektif Budi Rahardjo - Ahmad Firdaus Suryo Saputro; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to find out about independent campuses according to. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to the oral narrative from Budi Rahardjo's YouTube channel entitled